C# 5 First Look - Martinez, Joel; Martinez, Joel (Packt Publishing, 2012)
This will be a mix of concept introduction and examples, and with each new feature and enhancement we will give an example to the readers. C# 5 First Look will provide a gist of C# 5 to the readers. "C# 5 First Look" is for developers who want to learn about the latest version of C#. It is assumed that you have basic programming knowledge. Experience with prior versions of C# or the .NET Framework would be helpful, but not mandatory.